Understanding the achievement of benefits through use of Enterprise Content Management (ECM) systems in public sector organisations - Salamntu, Lumka Thami (Department of Information Systems, 2016)
Public sector organisations are implementing the Enterprise Content Management (ECM) system because of their large volume of unstructured content which led to documents being stored in various repositories. This made it difficult for such organisations to access, control and locate documents. ECM systems are therefore implemented to address the uncontrolled manner in which documents are saved, stored and accessed by employees. There were a number of other anticipated benefits. This study aims to explore and understand the achievement of benefits through the use of ECM systems and to determine the barriers preventing the benefits from being achieved in public sector organisations. The study used a qualitative research approach. Two cases of the public sector organisations were investigated in a cross-sectional study. Data was collected through semi-structured interviews and by viewing organisational documentation. Data was analysed using thematic analysis with elements of deductive and inductive approaches. An ERP benefits framework and the Enhanced Impact framework formed a theoretical base and were used as a lens for collecting and analysing data.